2010
DOI: 10.1371/journal.pgen.1001238
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domain of the Bacterial SSB Protein Acts as a DNA Maintenance Hub at Active Chromosome Replication Forks

Abstract: We have investigated in vivo the role of the carboxy-terminal domain of the Bacillus subtilis Single-Stranded DNA Binding protein (SSBCter) as a recruitment platform at active chromosomal forks for many proteins of the genome maintenance machineries. We probed this SSBCter interactome using GFP fusions and by Tap-tag and biochemical analysis. It includes at least 12 proteins. The interactome was previously shown to include PriA, RecG, and RecQ and extended in this study by addition of DnaE, SbcC, RarA, RecJ, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
161
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(166 citation statements)
references
References 54 publications
4
161
0
Order By: Relevance
“…Gene annotations for RecQ and RecS are different depending on the source of information. RecQ is encoded by an open reading frame named either recQ or yocI, whereas RecS is encoded by an open reading frame named either recQ or ypbC, again depending on the source used (77,350). B. subtilis RecQ shares the closest sequence homology to human WRN and E. coli RecQ, as it contains the highly conserved helicase domain, the RecQ helicase conserved region (RecQ-Ct), and the helicase and RNase D C-terminal domains (HRDC) (Fig.…”
Section: Recq Recs and Recjmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene annotations for RecQ and RecS are different depending on the source of information. RecQ is encoded by an open reading frame named either recQ or yocI, whereas RecS is encoded by an open reading frame named either recQ or ypbC, again depending on the source used (77,350). B. subtilis RecQ shares the closest sequence homology to human WRN and E. coli RecQ, as it contains the highly conserved helicase domain, the RecQ helicase conserved region (RecQ-Ct), and the helicase and RNase D C-terminal domains (HRDC) (Fig.…”
Section: Recq Recs and Recjmentioning
confidence: 99%
“…Recent work showed that the SSB protein targets several proteins, including RecQ, RecS, and RecJ, to the replication fork (77). Proteomic analysis of the interactome of SSB revealed numerous DNA repair proteins that bind SSB in vivo, including but not limited to RecQ, RecS, and RecJ (77) (see Table 3 for a complete list).…”
Section: Recq Recs and Recjmentioning
confidence: 99%
“…The recently postulated maintenance hub theory ascribes a speculative role for SSBs as a scaffold hub that recruits proteins involved in DNA metabolism and localises them to ssDNA [1].…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 C-terminal end of the arm, which binds to SSB interaction partners. Although this acidic region is well conserved in different species, their SSB interactomes are species dependent [1].…”
Section: Introductionmentioning
confidence: 99%
“…Akin to requirements for ATR activation, multiple RPAs are necessary to promote this exchange. Similarly, bacterial SSB interacts through its C-terminal tail with the recombination mediator RecO to facilitate loading of RecA onto ssDNA by RecFOR (Costes, et al, 2010;Inoue, et al, 2011). Another interesting interaction of SSB is its apparent competition with the RecA inhibitor RecX for the common ssDNA ligand.…”
Section: Interactive Role Of Rpa and Ssb In Dna Double-strand Break Rmentioning
confidence: 99%